Organization of nanostructures on the surface of Fe/Si - Jiang, Zongye (2013)
The use of Focused Ion Beam (FIB) in micromanufacturing has been prevalent since its invention in the 1970s. Nanoneedle structures were observed after ion sputtering using the FIB system on Fe deposited thin films. The surface modification of Fe deposited silicon resulted in a recent discovery of nanonipple structures by the bombardment of Ga+ ions. This fabrication process involved the FIB ion irradiation of Ga+ ions directed perpendicular to the substrate surface at implant energy of 30KeV.